Effects of earthworm hydrolysate on health status, laying performance, egg quality, and economic benefit of Cherry Valley laying ducks at the late phase of reproduction - Nguyen Vu Thuy Hong Loan; Ngo Hoang Thao Nhung (Veterinary Integrative Sciences)
The study aimed to evaluate the effect of the earthworm hydrolysate, including in a complete feed-based diet on laying performance, quality of commercial eggs, and economic return of Cherry Valley (CV) laying ducks at the late phase of reproduction. A total of 100 laying ducks at 48 weeks of age were randomly allocated to 2 dietary treatments, namely CTL (control, in which animals were fed a complete feed and EXP (experiment, in which ducks were fed complete feed and 100 mL of the earworm hydrolysate) and 5 replicates. Animals were kept in the net cage with an earth floor and 10 animals/cage. The results showed that laying rate, number of eggs per week, and egg weight were higher in the EXP than in the CTL, and lower feed consumed per 10 eggs in the EXP than in the CTL (P≤0.05); egg shape index, york percentage, Haugh unit, and shell thickness were higher in the EXP than in the CTL (P≤0.05). On the other hand, the profit was higher in EXP than in CTL. In conclusion, the inclusion of earthworm hydrolysate in a complete feed-based diet improved laying performance, egg quality, and economic return of CV laying ducks at the late phase of reproduction. The ducks fed earthworm hydrolysate diet had higher 4.7% laying rate, higher 6.1% selected egg rate for hatchery and 17% more profit than those fed control diet.